Public Law as Incentive Architecture: Rethinking Legal Design for Policy Uptake in Civil Service Reform - Ari Wibowo (Proceedings National Conference Sinesia, 2025)
This study examines why legal mandates in Indonesia’s civil service reform—despite being embedded in strong formal frameworks such as Law No. 5/2014—often fail to drive behavioral change among public officials. The objective is to investigate the cognitive, motivational, and institutional barriers that undermine legal compliance and to propose an alternative legal design grounded in behavioral insights. Methods: The research applies a Behavioral Law and Economics (BLE) approach through qualitative-descriptive analysis, combining doctrinal legal interpretation with institutional case studies across government agencies. Data is drawn from secondary sources, regulatory reviews, and literature on bureaucratic behavior and public policy compliance. Results: Findings show that regulatory failure is not merely technical but behavioral. Legal norms—such as merit-based recruitment, electronic performance systems, and open promotion—are often implemented symbolically. Barriers include regulatory overload, status quo bias, loss aversion, informal norms that compete with formal law, and political interference that distorts incentives. These dynamics result in path dependency and ritualistic compliance that weaken reform outcomes. Conclusions: This study proposes a reconceptualization of public law as incentive architecture, integrating nudges, defaults, and behavioral feedback into regulatory design. It recommends the reformulation of priority legal provisions, pilot testing of BLE-based interventions in civil service institutions, and the establishment of a behavioral legal design unit under the Ministry of Administrative Reform. Ultimately, the law’s effectiveness depends not on command-and-control logic but on its capacity to align with human cognition, motivation, and institutional context—allowing law to guide behavior intelligently and sustainably.